2018
DOI: 10.1039/c7cp07318f
|View full text |Cite
|
Sign up to set email alerts
|

Development and utility of a new 3-D magnetron source for high rate deposition of highly conductive ITO thin films near room temperature

Abstract: As transparent conductive films, indium tin oxide (ITO) materials are being extensively used as electrodes in various technological and optoelectronic applications. The demand for ITO films is firmly increasing because of the widespread market growth in these industries, but the available solutions only partly fulfill the prerequisites of high transmittance, low resistivity, large area process, cost-effective manufacturing, high growth rate and low-temperature process. The present work demonstrates a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…However, the facile deposition of such a brittle lm over transparent and exible substrates is extreme challenging for the electronics industry. [129][130][131][132][133] The commercial deposition of high-quality ITO also currently relies on the costly vacuum manufacturing approach. The liquid metal printing and post treatment was found to be a capable alternative technique for fabrication of the large-scale 2D ITO lm on the exible substrate at low temperature.…”
Section: The Squeeze Printing Techniquementioning
confidence: 99%
“…However, the facile deposition of such a brittle lm over transparent and exible substrates is extreme challenging for the electronics industry. [129][130][131][132][133] The commercial deposition of high-quality ITO also currently relies on the costly vacuum manufacturing approach. The liquid metal printing and post treatment was found to be a capable alternative technique for fabrication of the large-scale 2D ITO lm on the exible substrate at low temperature.…”
Section: The Squeeze Printing Techniquementioning
confidence: 99%
“…The TS touch-pressure sensor was fabricated using the following procedure. To improve the adhesion of the electrode layers, a 3-nm thick Al 2 O 3 layer was deposited via atomic layer deposition (ALD), followed by a 3-nm thick Cr layer that was deposited via e-beam evaporation, followed by deposition of GIG (Au-ITO-Au) layers using e-beam evaporation and advanced direct current (DC) sputter deposition 35 . PUDs with varying thicknesses were coated as the dielectric layer.…”
Section: Fabrication and Characterization Of Touch-pressure Sensorsmentioning
confidence: 99%
“…2). For the TS lower electrode with low piezoresistivity and optical transparency, various structures with ultrathin metal layers of Ti (adhesion layer, 3 nm in thickness)/Au layers of varying thicknesses (10, 20, and 30 nm) and stacked GIG structures of Au (5 nm)/ITO/Au (5 nm)-Ti (adhesion layer, 3-nm thick) were fabricated using e-beam evaporation (Ti and Au) and an advanced DC sputter deposition (ITO) 35 technique at 135°C. A comparison of the sheet resistance and optical transmittance of the ultrathin Au electrode indicated that both decreased as the Au thickness increased ( Fig.…”
Section: Transparent and Stretchable Electrodes On A 3d Micropatternementioning
confidence: 99%
“…Based on the geometry and orientation of the cathodes, the design of MS devices is known as conventional MS (CMS) or planar MS, 99,108 dual MS (DMS), 102,113 facing target MS (FTMS), 105 cylindrical MS (CYMS), 107 and three-dimensional MS (3DMS). [99][100][101]103,104,106,107 Furthermore, MS devices utilize a closed magnetic field geometry. The MS devices are divided into balanced and unbalanced configurations based on the formation of magnetic fields.…”
Section: Introductionmentioning
confidence: 99%